Past climate changes over South Korea during MIS3 and MIS1 and their links to regional and global climate changes. (10th June 2019) - Park, Sujeong; Lim, Jaesoo; Lim, Hyoun Soo
Abstract: To test past climate change in central Korea in terms of latitudinal differences over the Korean Peninsula, we reconstructed relative abundances between C3 and C4 plants in Hanam area based on sedimentary total organic carbon isotope values (δ 13 CTOC ) of a 2.8 m long trench in an archeological site and compared these data with climate changes at different latitudes of Korea. During marine isotope stage 3 (MIS3) corresponding to past 60, 000–25, 000 years, the millennial-timescale fluctuations of the δ 13 CTOC values in Hanam were more similar to those in Hongcheon located in the inner mountain area of central Korea than those in Cheollipo area in west coast of Korea. Periods with significantly decreased δ 13 CTOC values representing decreased C4 plants under wetter climates in these two inland areas are comparable with millennial-timescale Dansgaard–Oeschger (D-O) warming events recorded in Greenland ice cores, suggesting strong climatic teleconnection between East Asia and subpolar areas during the last glacial period. During MIS1 (Holocene), the changes in vegetation and climate in Hanam have been influenced by the long-term summer monsoon changes. Regarding past latitudinal change in aridity or humidity over Korea, during the middle Holocene, δ 13 CTOC values in areas of central South Korea gradually decreased, suggesting moving to a more humid climate. This is contrary to the increasing δ 13 CTOC values in southern South Korea indicating more dry climates. Furthermore, it is likely that there were two severe dry climates at different times at different latitudes (1000 cal BP in Hanam in northern South Korea and 2500 cal BP in Geoje in southern South Korea), suggesting possible different climate changes at millennial timescales over Korea.